Strategic Planning of Information System/Infromation Technology (Case Study: Gresik Regency Government Environment) - Muhammad Anwar Aini; Erma Suryani (Institut Teknologi Sepuluh Nopember, 2019)
Using IS (Information System)/IT (Information technology) has become the organization's need to carry out its operational activities and services. The government has also used IS/IT in carrying out its activities and services considering the benefits that are get, efficient, effective, and transparency to support good and clean governance. Gresik Regency does not yet have a master plan for implementing IS/IT so that what it needs cannot be managed. Gresik Regency needs a planned information technology-based system that can produce correct and prompt information. purpose of this study was to identify data and information needs in policy formulation and to develop an information system strategic plan in Gresik Regency. Basic concept used in compiling this research is the method proposed by John Ward and Joe Peppard. stages carried out start from analyzing the internal and external business environment of the organization, analyzing internal and external organization IS/IT, followed by identifying strategies and designing future portfolios. Method of analysis carried out uses several methods, among others, SWOT, Critical Success Factors, Value Chain, PEST, and Mc Farlan Strategic Grid. The results of this study is a blueprint of strategic planning that refers to the organization's business plan based on data obtained through the analytical methods used. It will integrate the information produced for administrative and public service needs. organization's strategic objectives in the form of superior prime service will be achieved by implementing an optimal improvement of data processing functions with the support of Information Technology. preparation of IS / IT strategic planning according to the resulting portfolio is expecting to be using in future strategic planning so it can give priority to the activities needed to get optimal results and based on its contribution to the objectives to be achieving